Positron Annihilation Lifetime Study of the Cubic Phases in The Ternary System of Didodecyldimethylammonium Bromide/ Water/ Hydrocarbon - Baijan, Abd. Halim (1999)

(untitled)
Positron annihilation lifetime technique (PAL) has become a standard technique especially for the investigation of defects in solids, fermi surface, phase transitions etc. The effectiveness of the method lies on the ability of the positron to sample selectively electron states in the media and highlighting them via its annihilation photons. It is now known that in amphiphilic system positron forms para and ortho-positronium atoms. The former has a lifetime of 125 ps and annihilates via two photons while the ortho-positronium atom has a lifetime of 140 ns and annihilates via three photons. Any localised factors such as those found during rearrangement of microstructures in amphiphilic systems can influence the ortho-positronium to annihilate prematurely. In this project Positron Annihilation Lifetime Method was used to study the cubic phases in the ternary system of didodecyldimethylamrnonium bromide (DDAB)/water /hydrocarbon. Three different systems of DDAB were measured i.e DDABI D201 Octane, DDABI D201 Tetradecane, and DDABI D201 Toluene. These systems were expected to provide information on the effect of molecular size and degree of penetration of the oil into the hydrophobic tail region and to influence the structure of the cubic phase. A fast-slow coincidence technique was used to measure the lifetime of positron that interacts with the surfactant medium. The result was analysed using POSITRONFIT programme. An attempt was made to identify the various symmetries by referring to alternative work on the same system. The inhibition constants, k' for the D -Schwarz of the mixtures of DDABI D201 Octane and DDABI D201 Toluene were found to be 2.54 and 0.92 respectively. On the other hand the P-Schwarz minimal surfaces for the mixtures ofDDABI D201 Octane gave an inhibition constant of 1.89 and for the mixtures of DDABI D201 Tetradecane an inhibition constant is 1.63. For other space groups such as the Ia3d space group in the DDABI D201 Toluene mixtures, k' was found to be 5.03 . Although the results is not constant from one sample to another, the positron method shows the sensitiveness of the changes in the microstructure phases. Thus the Positron Annihilation Lifetime Technique can be used as an alternative method in resolving phases in ternary surfactant systems.